Motivasi Belajar, Perilaku Belajar, Lingkungan Belajar dan Tingkat Pemahaman Akuntansi Selama Pandemi Covid-19 - Melyani, Ni Kadek Sri Ayu; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 33 No 12 (2023)DO - 10.24843/EJA.2023.v33.i12.p10, 2023)
The research aims to obtain empirical evidence of the influence of learning motivation, learning behavior and learning environment on the level of understanding of accounting during the Covid-19 pandemic at state and private universities that have accounting majors in Bali. The sampling method used was a nonprobability sampling method with accidental sampling technique. Data was collected using a survey method on 100 respondents. The analysis technique used is multiple linear regression analysis. The research results show that learning motivation, learning behavior and the learning environment have a positive influence on the level of understanding of accounting. This shows that the stronger the motivation to learn, the higher the level of understanding of accounting. The better learning behavior and supportive learning environment causes the level of accounting understanding of students majoring in accounting to increase. Keywords: Accounting Understanding; Learning Motivation; Behavior; Environment.